Case Report: Treatment of Femoral Non-union With Rib and Iliac Crest Autografts and rhBMP-2 in a Cat - Chung, Cheng-Shu; Lin, Lee-Shuan; Teo, Yi-Min (Frontiers in Veterinary Science, 2021)
A 5-year-old, intact male Bengal cat weighing 5.2 kg was referred for the fixation failure of a right femoral fracture. Multiple surgical revisions failed, and atrophic nonunion was diagnosed. The cat was then admitted for a final revision surgery using locking plate fixation in conjunction with rib and iliac crest autografts and recombinant human bone morphogenetic protein 2 (rhBMP-2). The fracture site was debrided and stabilized before filling the defect with 1.8 cm of rib bone autograft. The residual space in the defect was then filled with an iliac crest autograft. Finally, a 3 × 5 cm absorbable collagen sponge soaked with 0.5 mL of 0.2 mg/mL rhBMP-2 solution was placed around the defect. No significant complications were noted postoperatively. Bone healing was noted 2 months postoperatively, and it continued for 12 months. Although mild lameness remained, the cat's ambulatory function and quality of life were good. To the authors’ knowledge, this is the first case report of a clinical transplantation of a rib segment as an autograft in combination with rhBMP-2 in a cat with a large bone defect.